Vision preference value scale and patient preferences in choosing therapy for symptomatic vitreomacular interface abnormality - Marguerite O. Linz (2018)
© 2018 American Medical Association. All rights reserved. IMPORTANCE While symptomatic vitreomacular interface abnormalities (VIAs) are common, assessment of vision preference values and treatment preferences of these may guide treatment recommendations by physicians and influence third-party payers. OBJECTIVE To determine preference values that individuals with VIA assign to their visual state and preferences of potential treatments. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional one-time questionnaire study conducted between December 2015 and January 2017, 213 patients from tertiary care referral centers in Thailand, the United Kingdom, and the United States were studied. Patients with symptomatic VIA diagnosed within 1 year of data collection, visual acuity less than 20/20 OU, and symptoms ascribed to VIAs were included. Data were analyzed from January 2017 to November 2017. MAIN OUTCOMES AND MEASURES The primary end points were overall mean preference value that individuals with VIA assigned to their visual state and patients' preferences for potential treatments. Preference values were graded on a scale from 0 to 1, with 0 indicating death and 1 indicating perfect health with perfect vision. RESULTS Of the 213 included patients, 139 (65.3%) were women, and the mean (SD) age was 65.6 (7.7) years. Diagnoses included epiretinal membrane (n = 100 [46.9%]), macular hole (n = 99 [46.5%]), and vitreomacular traction (n = 14 [6.6%]). The mean (SD) vision preference value was 0.76 (0.15), without differences identified among the 3 VIA types. More participants were enthusiastic about vitrectomy (150 [71.1%]) compared with intravitreal injection (120 [56.9%]) (difference, 14.2%; 95% CI, 5.16-23.3; P = .002). Adjusted analyses showed enthusiasm for vitrectomy was associated with fellow eye visual acuity (odds ratio, 10.99; 95% CI, 2.01-59.97; P = .006) and better-seeing eye visual acuity (odds ratio, 0.03; 95% CI, 0.001-0.66; P = .03). Overall enthusiasm for treatment was associated with fellow eye visual acuity (odds ratio, 7.22; 95% CI, 1.29-40.40; P = .02). Overall, most participants (171 [81.0%]) were enthusiastic about surgery, injection, or both. CONCLUSIONS AND RELEVANCE Study participants reported similar preference values among 3 types of VIAs. The data suggest that most patients with these conditions would be enthusiastic about undergoing vitrectomy or an injection to treat it, likely because of the condition's effect on visual functioning, although there may be a slight preference for vitrectomy at this time.